Dancing With Non-duality for Healing Through the Shadows of the COVID-19 Pandemic - Bai, Heesoon; Berry, Kevin; Haber, Jesse; Cohen, Avraham (Frontiers in Education, 2021)
The COVID-19 pandemic has unleashed torrents of global suffering at a devastating scale, necessitating a strong response to alleviating suffering. This paper begins with noting that the conventional approach to suffering in North America is to be positive and not to be negative. The paper summarily explores the philosophy of positive psychology underlying the first- and the second-wave of positive psychology, commenting on the evolution from dualism and a binary conceptualization in the first wave (PP 1.0) to a nondualism of integrating binaries in the second wave (PP 2.0). PP 2.0’s enhanced therapeutic efficacy is noted for its nondual framework. The paper then explores and suggests a different conceptualization possibility of nonduality, fundamental nonduality, that is related to but distinct from the one in PP 2.0. A case is made that fundamental nonduality has a radical possibility of therapeutic efficacy. Being consistent with the philosophy of nonduality, further suggestions are made that nonduality of PP 2.0 and fundamental nonduality can be therapeutically deployed together for greatest efficacy. The exploration contained in the paper is largely philosophical, arts-based, and autobiographical, creating an enacted and lived experience of applying theory to practice.